Tubulin-based polymorphism genome profiling: a novel method for animal species authentication in meat and poultry. (April 2020) - Gianì, Silvia; Di Cesare, Verdiana; Gavazzi, Floriana; Morello, Laura; Breviario, Diego
Abstract: We present a new method for the authentication of the biological identity of raw meat and processed meat products that is based on length polymorphism found in the introns of the members of the animal beta-tubulin gene family. The method, denominated aTBP for animal Tubulin-Based-Polymorphism, is shown to be capable of assigning an exclusive genomic fingerprinting to ten different animal species, eight of which are largely consumed as food products. Besides an exclusive DNA profiling, each species is characterized by the presence of specific diagnostic fragments, that assist their selective recognition in admixtures and products sold in the market. The aTBP method is also shown to be effective in both DNA/DNA and weight/weight mixtures where the presence of the low abundance species can be detected at the level of 0.5% and 1% respectively. Detection by aTBP genome profiling is also obtained from either frozen/thawed or cooked samples. The composition of 25 market products made by meat was also assessed with respect to what declared in the label. The results are discussed with reference to biosurveillance and disclosure of frauds and contaminations in comparison with other DNA-based diagnostic methods currently used. Highlights: The aTBP method for species authentication in animal food products is presented. The method is based on intron DNA polymorphisms of the nuclear beta-tubulin genes. The aTBP method successfully applied to raw materials, mixtures and market products. The aTBP method produces a DNA profile that identifies ten animal species. The aTBP method is capable of recognizing species adulteration at a 1% w/w level.